Water absorption and dough rheology of high amylose wheat flour in relation to bread making quality and digestibility - Smith, Riley (My University, 2025)
The health benefits of dietary fiber (DF) are well recognized. Yet, a large gap still exists between the recommended daily intake (28-42 g / day) and the amount that is actually consumed in the US and similarly in the world. Wheat-based foods (e.g. bread, pasta, noodles) supply about 20% of food energy for the world population. People are eating more whole grains, but many consumers still prefer foods made from refined wheat flour. These foods are low in DF and resistant starch (RS). RS functions as DF; as it is a starch fraction that is not digested or absorbed in the small intestine in healthy individuals rather fermented in the large intestine, producing short chain fatty acids with health benefits. It is difficult to make wheat-based staple foods with high DF and RS, retaining low or slow digestion, and have good sensory properties. The starch in normal wheat (about 25-30% amylose) is highly digestible. Recently, a high-amylose wheat (HAW) was developed. This is game-changing because the significant increase in amylose results in a high RS content (low digestibility) in refined wheat flour. A knowledge gap pertaining to the increased amylose content in relation to the dough rheology of HAW flour has been identified for this study. The objectives of the first part of this study were to investigate the water absorption and viscoelastic properties of hard red spring (HRS) HAW flour dough (58.90% amylose content), comparing with normal HRS and hard red winter (HRW) flour doughs. The regular wheat flours showed an average of 62.8% compared to HAW’s 79.1% for optimal water absorption across all empirical mixing methods. The effects of arabinoxylan content on water absorption of wheat flour were also examined. The colorimetric measurement of arabinoxylans in each flour revealed that the HAW flour had 1.05-1.39% more total arabinoxylans. Solvent retention capacity of sucrose and frequency sweep assessments before and after xylanase hydrolysis revealed that arabinoxylans were contributing to the heightened water absorption. The dough rheological measurements also showed an increase in absorption time as the larger amount of water was distributed, resulting in a tougher dough at the beginning of mixing. Additionally, the HAW flour produced a dough that had statistically similar viscoelasticity to normal wheat doughs when optimally hydrated. With the HAWs Mixograph and Farinograph’s 4 min and 5.62 min dough development times there were no statistical differences identified compared to the HRS wheat flour. The use of HAW flour and solubilization of water unextractable arabinoxylans also decreased the doughs resistance to deformation and recoverable strain. The high level of amylose in wheat flour leads to increases of RS and DF contents. The objectives of the second part of this study were to determine the optimal water absorption of HAW flour for bread making quality and starch digestibility. Bread made with HAW flour had a decreased volume, crumb structure, and lightness while increasing initial firmness compared to normal HRS and HRW wheat breads. The HAW bread had a specific volume of 4.61ml/g compared to the normal wheats average 5.91ml/g, resulting from a significant decrease in C-Cell number of cells data with 6610.3 cells compared to regular wheats averaged 7371.8 cells identified. The textural profile analysis of the bread crumb also revealed the bread crumb to be firmer than the regular wheat breads at the end of cooling. The use of DSC and XRD analysis showed the increased firmness to be associated with the heightened amylose content rapidly re-associating during the cooling period, increasing short-term retrogradation, while the limited amylopectin retrogradation produced insignificant long-term retrogradation. Xylanase treatment showed significant improvement to long-term firmness in breads. The in-vitro digestibility revealed a significant decrease in digestibility of starch in bread made with HAW flour due to significant increases in re-association (retrogradation) of amylose and lipid complexing of amylose molecules.
Keywords: High-amylose; Arabinoxylan; Rheology; Baking; Resistant-starch; Digestibility